Lembaga Wali Nanggroe: Peran, Fungsi dan Strategi Resolusi Konflik Aceh Pasca Perdamaian - Zulham Ibrahim (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
Wali Nanggroe Institution is an institution of cultural authority as the unifier of the people that is independent, authoritative, and has the authority to develop and oversee the implementation of the life, adat (custom), language, the award of titles and honors, and adat rites. This research was conducted in Banda Aceh city using a qualitative method. The concept used was Wali Nanggroe, the theories of strategy, conflict resolution, and political communication theories to resolve local conflicts and analyze Wali Nanggroe neutrality in resolving conflicts in Aceh. The data were obtained by observation technique and interview (questionnaires and voice records). The results found that the Wali Nanggroe Institution does not implement a strategy in resolving conflicts both local conflicts and other conflicts in local institutions. Also, Wali Nanggroe does not hold political communication to resolve the conflicts. Besides, as a mediator, Wali Nanggroe is unfair to resolve the conflicts among local institutions due to some causes; emotional attachment between Wali Nanggroe and Members of Parliament at Aceh Provincial House of Representatives (DPRA) from Aceh Party Faction, tend to maintain the reign of Wali Nanggroe, and procedural problems in Wali Nanggroe election.